School Vouchers in Practice: Competition Won't Hurt You! - F. Mikael Sandström; Fredrik Bergström (The Research Institute of Industrial Economics (IUI), 2002)
An important issue in the debate on voucher systems and school choice is what effects competition from independent schools will have on public schools. Sweden has made a radical reform of its system for financing schools. Independent and public schools operate on close to equal terms under a voucher system covering all children. Sample selection models are estimated, using a data set of about 28 000 individuals. In addition, panel data models are estimated on 288 Swedish municipalities. The findings support the hypothesis that school results in public schools improve due to competition.
Keywords: H42; H52; I28; L19; 330; Public Education; Independent Schools; Student Achievement; School Vouchers; School Choice; Sample Selection Model; Panel Data Model; Instrumental Variable Estimation; Bildungswesen; Bildungsniveau; Allgemeinbildende Schule; Schätzung; Schweden